The power mean and the logarithmic mean - Christopher Olutunde Imoru (International Journal of Mathematics and Mathematical Sciences)
In a very interesting and recent note, Tung-Po Lin [1] obtained the least value q and the greatest value p such that Mp<L<Mqis valid for all distinct positive numbers x and y where Ms=(xs+ys2)1s   and   L=x−yIn x-In y